Workers and Canadian History - Kealey, Gregory S. (McGill-Queen's University Press, 1995)
Workers and Canadian History is a collection of twelve essays by Gregory Kealey, the recognized Canadian leader in the growing field of working-class history. Available for the first time in a single volume, the essays provide an extensive study of various trends and themes in Canadian labour and working-class history, covering debates, major developments in historiography, and key events in the nineteenth and twentieth centuries. Kealey provides an overview of the study of workers in Canada as well as in-depth examinations of two of the field's leading scholars, political economist Clare Pentland and Marxist historian Stanley Bréhaut Ryerson. He analyses the development of Canadian labour history in particular and social history in general, and provides detailed empirical studies of the Orange Order in Toronto, printers and their unions, the Knights of Labor, and the Canadian labour revolt of 1919. The collection concludes with three synthetic views of Canadian working-class history focusing on the labour movement, the role of strikes, and attempts by the state to manage class conflict. --Publisher's description. Contents: Part 1: Antecedents. Writing about Labour -- H.C. Pentland and Working-Class Studies -- Stanley Bréhaut Ryerson: Canadian Revolutionary and Marxist Historian. Part 2: Debates. Labour and Working-Class History in Canada: Prospects in the 1980s. -- The Writing of Social History in English Canada, 1970-84. Part 3: Studies of Class and Class Conflict. Orangemen and the Corporation: The Politics of Class in Toronto during the Union of the Canadas -- Work Control, the Labour Process, and Nineteenth-Century Canadian Printers -- The Bonds of Unity: The Knights of Labor in Ontario, 1880-1900 / Gregory S. Kealey and Bryan D. Palmer -- 1919: The Canadian Labour Revolt. Part 4: Overviews. The Structure of Canadian Working-Class History -- Strikes in Canada, 1891-1950 / Gregory S. Kealey and Douglas Cruikshank -- The Canadian State's Attempt to Manage Class Conflict, 1900-48.
Keywords: Canada; History; Labor Unions; Labor movement; Strikes and lockouts; Working class